2021
DOI: 10.1159/000517309
|View full text |Cite
|
Sign up to set email alerts
|

Formative Evaluation of the Families SHARE Disease Risk Tool among Low-Income African Americans

Abstract: <b><i>Introduction:</i></b> Family Health Histories (FHH) have been endorsed by the surgeon general as a powerful yet underutilized tool for identifying individuals at risk for complex chronic diseases such as diabetes, heart disease, and cancer. FHH tools provide a mechanism for increasing communication about disease history and motivating behavior change to reduce disease risk. A critical gap in translation efforts includes a lack of research that adapts and evaluates tools for low-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Providing health information in ways that are accessible, regardless of educational attainment, is important for that information to be useful for all (McClure et al, 2016). Moreover, since sickle cell disproportionately impacts those of African and Hispanic heritage, it is important to tailor educational materials to be culturally relevant (de la Haye et al, 2021). Such factors highlight the importance of engaging patients and their families in developing educational materials that are accessible and culturally relevant to those coping with sickle cell within their families.…”
Section: Discussionmentioning
confidence: 99%
“…Providing health information in ways that are accessible, regardless of educational attainment, is important for that information to be useful for all (McClure et al, 2016). Moreover, since sickle cell disproportionately impacts those of African and Hispanic heritage, it is important to tailor educational materials to be culturally relevant (de la Haye et al, 2021). Such factors highlight the importance of engaging patients and their families in developing educational materials that are accessible and culturally relevant to those coping with sickle cell within their families.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a need to expose the public to clinical applications of genetics and community-based genomics education programs in addition to basic technical terms. 36,37 Participants in the 2021 sample were least familiar with the term “genome,” indicating a need for increased awareness of recent advances in genomic and personalized medicine. It is important to note, however, that familiarity with a term does not equate to comprehension and as such, it is important to also explore individuals’ factual knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Like the 2013 sample, participants in 2021 were most familiar heredity This suggests a need to expose the public to clinical applications of genetics and community-based genomics education programs in addition to basic technical terms. 36,37 Participants in the 2021 sample , indicating a need for increased awareness of recent advances in genomic and personalized medicine. It is important to note, however, that familiarity with a term does not equate to On average, participants in the 2021 sample scored higher in the knowledge module, meaning they more accurately identified sixteen factual genetics statements as true or false.…”
Section: Changes In Genetic Literacy Over Timementioning
confidence: 99%
“…With respect to T2 and T3, or translational research, inclusion of minoritized populations in behavioral genomics research requires critical considerations for design and implementation strategies. Families SHARE is a toolkit, comprised of a workbook, community education program, and video, with the goal of increasing families’ genomic health literacy as it relates to family health history of complex conditions with behavioral risk factors and encourage family engagement around conversations about risk and risk-reducing behaviors ( Koehly et al, 2015 ; de la Haye et al, 2021 ; Wilson, et al, 2016 ). The Families SHARE program has been adapted to multiple geographical and cultural contexts and is an example of a scientifically and culturally diverse collaboration which has allowed translation to reach various populations including White and historically under-represented populations in biomedical research in the United States, immigrant and ethnically diverse communities in Australia, and communities in rural Nigeria, Africa.…”
Section: Four Possible Solutionsmentioning
confidence: 99%
“…The partnerships can enable future research—such as increase participation in sequencing research, returning results, and other educational and intervention opportunities—as they represent trusted pathways for genetic and genomic-related activities. Moreover, participants who engaged in Families SHARE at the Washington, DC study site reported feeling empowered by using and sharing the Families SHARE workbook with family and healthcare providers ( de la Haye et al, 2021 ). This points to the importance of bi-directional relationships such that scientific teams are supporting communities and communities are benefiting from the research.…”
Section: Four Possible Solutionsmentioning
confidence: 99%